فاعلية برنامج تدريبي في تنمية التعبير الكتابي والاستيعاب القرائي - المشاقبة, رامي (جامعة الوادي University of Eloued, 2017)
هدفت الدراسة الحالية الى التعرف على فاعلية برنامج تعليمي في التمثيل المعرفي والاستيعاب القرائي لدى طلبة صعوبات التعلم الملتحقين بغرف المصادر. وتكونت عينة الدراسة من (36) طالباً من طلبة الصف الرابع في المدارس الأساسية في لواء البادية الشمالية الشرقية والذين يعانون من صعوبات في التعلم في التعبير الكتابي والاستيعاب القرائي. وقد استخدم الباحث المنهج التجريبي لمناسبته لطبيعة الدراسة وأهدافها وتم تقسيمهم الى مجموعتين احداهما تجريبية والاخرى ضابطة متساويتين ومتجانستين في العمر الزمني ومستوى التعبير الكتابي ومستوى الاستيعاب القرائي. حيث أظهرت نتائج الدراسة الحالية فعالية البرنامج التدريبي المستخدم في تنمية التعبير الكتابي والاستيعاب القرائي لدى طلبة ذوي صعوبات التعلم، واختتم البحث بمناقشة نتائج الدراسة، وعرض مجموعة من التوصيات والبحوث المستقبلية المقترحة ذات العلاقة بموضوع البحث الحالي. This study aims to effectiveness the impact of the application of an educational program in Written expression and reading comprehension among students learning disabilities enrolled rooms sources. The study sample consisted of 36 students from the fourth grade students in basic schools in the District of north-eastern desert, And those with learning difficulties in written expression and reading comprehension. Researcher experimental method has been used for the appropriateness of the nature and objectives of the study were divided into two groups, one experimental and the other officer equal and homogeneous in chronological age and level of written expression and the level of reading comprehension. Where the results of the current study, the effectiveness of the training program the user has shown in the development of written expression and reading comprehension among students with learning difficulties, and concluded Find discuss the results of the study, presented a set of recommendations proposed and future research related to the topic of current research.
لدى طلبة ذوي صعوبات التعلم بالأردن
مقال
Keywords: البرنامج التدريبي؛ التعبير الكتابي؛ الاستيعاب القرائي; Effectiveness of the program; Written expression; Reading comprehension